Regla File Storage System - Hulda Lilja Hannesdóttir 1994-; Jóhanna María Svövudóttir 1992-; Sigrún Tinna Gissurardóttir 1990-; Unnur Sól Ingimarsdóttir 1995- (2018)
Regla skalavistunarkerfi is a software that four students designed and created for Fakta ehf for their final project towards their BSc degree in Computer Science at Reykjavík University. The system is an add on to Fakta’s business solutions. The main purpose of the system is to make it easy to store and organize files in such a way that makes it fast to retrieve them later.